MUSICAL EVALUATION OF PAUL KLEE’S - Aysegul Terkan Gurcan; Dr. Mohd Jamil Mat Isa (Journal of Islamic, Social, Economics and Development, 2022)
Throughout history, many branches of science and art have been the subject of interdisciplinary studies. Research on sound and color has been going on since ancient times, but especially in the 19th century, the relationship between painting and music contributed to the creation of important works in both art branches. From past to present, artists have tried to establish a relationship between painting and music with their interest in different arts, their search for new pursuits, or the effect of synesthesia. In this study, the interaction of these two art branches with each other is mentioned. At the same time, Paul Klee's painting "Light and Shadow (1935)", one of the most important artists of the 19th century, was examined and the effect of music on his paintings was examined. This painting by Paul Klee is also one of the best examples of interdisciplinary studies in the history of art. This research is a descriptive-based, qualitative study created by document review and literature review.